Características botánicas y climatológicas de los principales materiales de siembra de palma aceitera (Elaeis guineensis Jacq.), en el Ecuador. - Cruz Alvarado, Jackson Nicanor (2022)
This paper details the botanical and climatological characteristics of the main oil palm (Elaeis guineensis Jacq) planting materials in Ecuador. This oilseed is native to Africa and is the plant that extracts more oil per unit area than other vegetables, in addition to making products such as; biodiesel, palm kernel cake, soaps, olein, fiber, solid organic fertilizer among other things. One of the main problems is to know which variety of palm to cultivate depending on the agricultural area and to obtain advantages in agronomic management, climatological factors and resistance to diseases that are limiting in cultivation. Therefore, this document aims to identify the botanical and climatological characteristics of the main oil palm planting materials in Ecuador. To carry out this research project, an information consultation methodology was used in; theses, scientific articles, web pages, books, university repositories, newspapers, posters, brochures, etc. The African palm grows at an average temperature of 21°C, with a maximum height of 500 meters above sea level, rainfall of 1800 mm, heliophany of 1500 light hours. It is established in clay loam soils. The Iniap-Tenera hybrid is adapted to palm growing areas and has excellent oil extraction and heavy bunches, as well as Compacta for Ghana, which has reduced stem growth similar to Amazon, being highly resistant to PC Deli x La Mé and Deli x Ghana are highly resistant to drought, the latter being planted at high altitudes.